Beginning JSON - Smith, Ben 1975- (The expert's voice in web development, 2015)
Beginning JSON is the definitive guide to JSON, JavaScript Object Notation, today's standard in data formatting for the web. The book starts with the basics, and walks you through all aspects of using the JSON format.